Shari'a councils and Muslim women in Britain: rethinking the role of power and authority - Walker, Tanya (Muslim minorities, 2017)
Introduction -- The sharia councils, the women, and some methodological concerns -- The question of authority -- The women in context : the web of power -- Tactics of power -- Conclusion